HUBUNGAN PERILAKU NEGATIF (MENYIMPANG) SISWA DENGAN PRESTASI BELAJAR SISWA KELAS XI DI TAMAN MADYA (SMA) TAMAN SISWA PEMATANGSIANTAR - Aris Owen Alfaro Malau; Binsar Tison Gultom; Benjamin Albert Simamora (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the relationship between negative (deviant) student behavior and the learning achievement of grade XI students at Taman Madya (SMA) Tamansiswa Pematangsiantar. This type of research is quantitative research with a correlational approach. The population of this study is grade XI students at Taman Madya (SMA) Tamansiswa Pematangsiantar with a total of 261 students. The research sample was 43 students. The sample was determined from students who had been recorded in BK (Guidance Counseling) records as a result of behavior that was not in accordance with school rules with a total of 43 students. The data collection technique used is a questionnaire (questionnaire).The results of this study state that there is a relationship between negative (deviant) student behavior and student learning achievement in class XI at Taman Madya (SMA) Tamansiswa Pematangsiantar. The relationship is evidenced by the results of the sig value of 0.032 <0.05 which indicates a relationship between the two variables, as well as evidenced by the results of the pearson correlation which has a negative effect of 0.327. This value after being interpreted using the correlation interpretation criteria, the pearson correlation is in the range (0.20-0.399) which is interpreted as included in the category of having a low correlation which means that the two variables are clearly related but small.